Pengaruh Expertise, Trustworthiness, dan Attractiveness Influencer, Terhadap Brand Expected Value Terhadap Purchase Intention pada Studi Kasus Influencer Dr Tirta dan Merek Sepatu Lokal - Dennis Trama Karindra; Usep Suhud; Meta Bara Berutu (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study aims to examine and analyze the influence of influencer expertise, trustworthiness, and attractiveness on brand expected value and purchase intention, using the case of Dr. Tirta and local footwear brands. The study involved 250 respondents who had previously viewed local footwear review content by Dr. Tirta on social media and were domiciled in DKI Jakarta. The analytical methods employed included validity and reliability testing using SPSS, as well as model fit and hypothesis testing using AMOS 29. The data were analyzed using Structural Equation Modeling (SEM). The findings indicate that expertise has a direct effect on purchase intention and also significantly influences brand expected value, along with the attributes of trustworthiness and attractiveness. However, brand expected value does not have a significant effect on purchase intention, suggesting the presence of other variables that influence this relationship. Therefore, factors such as brand preference and promotional strategies remain important in shaping consumer purchase decisions.